Malignancy knows no boundaries. (5th August 2013) - Batra, Sandeep; Vaid, Ashok K; Bhargava, Rahul; Singh, Amanjeet
Abstract : A 47-year-old woman presented with ascites. There was history of large volume paracentesis and the drained ascitic fluid was found to be positive for malignant cells. Clinical examination revealed a soft tissue nodule over the skin of right iliac fossa and a small umbilical nodule besides presence of ascites. In addition, the patient had a breast lump of 2×2 cm in upper quadrant of right breast. Biopsy from the abdominal wall nodule revealed a malignant tumour with dense desmoplastic response. The tumour cells were pancytokeratin, CA125, WT1 positive and CDX2, CD10, villin, calretinin negative; thus immunohistochemically suggesting a primary tumor arising from ovary. Biopsy from breast lump showed malignant epithelial cells present in sheets with stromal dysplasia. Immunohistochemically tumour cells were positive for CK7. CA125, WT1, thus favouring a metastatic carcinoma to breast with possible primary arising from ovary.